Why to Restore Mangroves? An Economic Valuation - Kathiresan, K. (Indian Forester, 2021)
Despite increasing pressures, the mangrove forest in India has increased by 54 km2 in the two years from 2017 to 2019. This increase is estimated here for ecological services and economic values and this is multifold greater than the cost of plantation, and hence it is a cost-effective venture. However, 40.6% of mangroves in India are of open type and degrading, and hence, it is s uggested to rehabilitate the degrading mangroves especially in unprotected areas and to achieve a target of 6000 km2 within 10 years for restoring the ecosystem service and enhancing the economic value.